Использование измельченных семян льна в рецептуре слоеных хлебобулочных изделий - Андронович, Галина Михайловна; Бондаренко, Юлия Викторовна (My University, 2021)
The development of enriched and functional products is a priority in the development of the modern assortment of the food industry. The article discusses the possibility of using crushed yellow flax seeds in the recipe for puff bakery products. Flax seeds are a source of biologically active substances important for human health: alpha-linolenic acid, lignans and soluble dietary fiber. It was found that it is advisable to use crushed yellow flax seeds for enrichment of puff bakery products in an amount of up to 15% by weight of flour. This makes it possible to enrich the products with physiologically functional flax ingredients and obtain good quality products. The use of crushed flax seeds for enrichment of puff bakery products also made it possible to reduce the prescription amount of margarine per puff pastry from 35% to the dough mass to 20%.

В статье рассмотрена возможность применения измельченных семян льна желтой окраски в рецептуре листовых хлебобулочных изделий. Установлено, что для максимального обогащения изделий физиологически функциональными ингредиентами льна и получения при этом их хорошего качества, рекомендовано дозировку измельченных семян льна до 15% к массе муки. Использование в рецептуре измельченных семян льна также позволило снизить рецептурное количество маргарина на слоеное тесто с 35% до массы теста до 20%.
Keywords: листовые хлебобулочные изделия; семена льна; тесто; физиологично-функциональные ингредиенты; кафедра технології хлібопекарських і кондитерських виробів; puffed bakery products; flax seeds; dough; physiologically functional ingredients